Use of Cosmetic Creams and Perception of Natural and Eco-Friendly Products by Women: The Role of Sociodemographic Factors - Marina Leite Mitterer-Daltoé; Vaniele B. Martins; Cristiane R. B. Parabocz; Mário A. A. da Cunha (Cosmetics, 2023)
The present work seeks to understand the use of cosmetic creams and the perception of natural and eco-friendly products by women and to explore the impacts of their personal characteristics. The study was designed using two approaches: (i) an investigation into the role of personal characteristics on the frequency of use and amount spent on cosmetic creams; and (ii) an understanding of the perception of natural and eco-friendly cosmetic creams by the use of check-all-that-apply (CATA) questions. Results showed that scholarity has a strong influence on the use of cosmetic creams; women with a postgraduate education reported higher frequency of use and spending on cosmetic creams and showed an awareness of natural and eco-friendly cosmetics. The subject of natural and eco-friendly cosmetic creams is not something that most of the women that participated were aware of, and the CATA technique proved to be a valuable tool to discover this.